Four-row APPLE-Knot undulator mechanical design and test piece studies for High Energy Photon Source. (1st August 2022) - Huang, Y.S.; Yang, Y.W.; Li, X.Y.; Lu, H.H.; Gong, L.L.; Li, Y.H.; Sun, Y.J.; Chen, W.; Sun, S.C.; Li, Z.Q.; Zhao, S.T.; Zhang, L.; et al.
Abstract: A four-row APPLE-Knot undulator is under developing in the High Energy Photon Source to get polarization adjustable synchrotron radiation and reduce on-axis heat load, because of the exotic magnetic field design, its construction faces challenges in mechanical design of frame, magnet blocks holder and integral field shimming method. In this paper, a mechanical design for APPLE-Knot undulator has been posed and structural deformation has been analysed, a test piece has been manufactured to test the physical design as well as magnetic holder design, integral field shimming method has also been described and realized, the result presents a good repeatability. It's a practical design of four-row APPLE-Knot undulator for the High Energy Photon Source.